Combined AFM/Raman Studies of Heterogeneous Polymer Materials. Issue 25 (6th June 2016) - Surtchev, Marko; Wall, Mark; Magonov, Sergei
ABSTRACT: Compositional imaging of several immiscible polymer blends was examined with the combination of AFM-based mechanical and electric modes with chemically-specific Raman mapping. Results showed that these methods substantially complement each other in comprehensive characterization of surface morphology by helping to identify a composition of top surface and sub-surface materials in polymer heterogeneous systems.